Analisis Pesan Dakwah Pada Novel Si Anak Pemberani Karya Tere Liye - Tami, Fadillah Winda; Razzaq, Abdur; Muzaiyanah, Muzaiyanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Preaching is essentially an act of faith performed by Muslims, such as preachers, media, messages, audiences, methods, and responses. One way to carry out da'wah is by reading literary works. To ensure that da'wah can achieve its goals and objectives optimally. Literature is a product of art that discusses human values and how to use language to express life. The purpose of this research is to discover and analyze Tere Liye's novel